2018
DOI: 10.1039/c8lc00694f
|View full text |Cite
|
Sign up to set email alerts
|

An integrated microfluidic/microelectrode array for the study of activity-dependent intracellular dynamics in neuronal networks

Abstract: A microfluidics/MEA platform was developed to control neuronal activity while imaging intracellular dynamics within reconstituted neuronal networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 47 publications
0
84
0
Order By: Relevance
“…Once a neural circuit is implemented on chip, the possibility to record the electrical activity of the neuronal populations in real time is an essential requirement to acquire a basic understanding of the network functionality. To this aim, several studies have successfully demonstrated the integration of commercial or custom-made multielectrode arrays (MEAs) within microfluidic chips [ 53 , 133 , 134 , 135 , 136 , 137 , 138 ]. In details, MEAs are composed of a set of microelectrodes typically arranged in a matrix configuration, that enable to record extracellular activity of neuronal populations from multiple sites simultaneously in a noninvasive way [ 139 , 140 , 141 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Once a neural circuit is implemented on chip, the possibility to record the electrical activity of the neuronal populations in real time is an essential requirement to acquire a basic understanding of the network functionality. To this aim, several studies have successfully demonstrated the integration of commercial or custom-made multielectrode arrays (MEAs) within microfluidic chips [ 53 , 133 , 134 , 135 , 136 , 137 , 138 ]. In details, MEAs are composed of a set of microelectrodes typically arranged in a matrix configuration, that enable to record extracellular activity of neuronal populations from multiple sites simultaneously in a noninvasive way [ 139 , 140 , 141 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
“…For instance, Moutaux et al developed an on-chip platform that combines a compartmentalized microfluidic device with a dedicated MEA to selectively record electrical activity in presynaptic axonal projections and postsynaptic neuronal targets, while simultaneously studying intracellular dynamics via high-resolution videomicroscopy ( Figure 5 a) [ 136 ]. The microfluidic platform consists of two opposite neuronal chambers connected via an intermediate synaptic chamber through microchannels of different lengths, i.e., 500 µm for presynaptic neurons and 75 µm for postsynaptic neurons [ 132 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
“…Because these are recorded noninvasively, repeated measurements can be achieved over time in either brain slices or tissue culture preparations. [259] Based on the design of the microfluidic system and MEA, research can range from investigating intracellular dynamics in a single axon [260] to propagation between neuronal sub-populations (e.g., cortical-thalmic) in a co-culture system. [261] Although not part of a microfluidic chip, MEAs have also shown utility in drug screening applications such as the evaluation of neurotoxic compounds.…”
Section: Technology and Systems Integration In Microfluidic Platformsmentioning
confidence: 99%
“…The device has three microfluidic chambers, presynaptic, synaptic, and postsynaptic chambers (each) with axonal, reference, and postsynaptic electrodes to record the activity of single projecting axon. These presynaptic axons were recorded selectively by placing electrodes under the presynaptic chamber, and this study was further extended to study calcium dynamics [196]. Figure 20 depicts a microfluidic DEP device consisted of a PDMS microfluidic chip with ring-shaped indium tin oxide microelectrode array.…”
Section: Micro/nanofluidic Devices For Single-neuron Analysismentioning
confidence: 99%